2019
DOI: 10.1128/msphere.00047-19
|View full text |Cite
|
Sign up to set email alerts
|

Kinome-Wide RNA Interference Screening Identifies Mitogen-Activated Protein Kinases and Phosphatidylinositol Metabolism as Key Factors for Rabies Virus Infection

Abstract: Throughout the rabies virus (RABV) infectious cycle, host-virus interactions define its capacity to replicate, escape the immune response, and spread. As phosphorylation is a key regulatory mechanism involved in most cellular processes, kinases represent a target of choice to identify host factors required for viral replication. A kinase and phosphatase small interfering RNA (siRNA) high-content screening was performed on a fluorescent protein-recombinant field isolate (Tha RABV). We identified 57 high-confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Tha-eGFP and Th2P-4M-eGFP harbour the same genetic background except for two mutations introduced in viral P-protein (W265G, W287V) and four mutations introduced in the M protein (R77K, D100A, A104S, M110L) (10,31,32). For imaging purposes, the eGFP sequence was introduced after the M protein gene sequence as described previously (35). (B) Representative immunofluorescence pictures of SK-N-SH, SVGp12, and HMC3 cells upon infection with Tha-eGFP and Th2P-4M-eGFP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tha-eGFP and Th2P-4M-eGFP harbour the same genetic background except for two mutations introduced in viral P-protein (W265G, W287V) and four mutations introduced in the M protein (R77K, D100A, A104S, M110L) (10,31,32). For imaging purposes, the eGFP sequence was introduced after the M protein gene sequence as described previously (35). (B) Representative immunofluorescence pictures of SK-N-SH, SVGp12, and HMC3 cells upon infection with Tha-eGFP and Th2P-4M-eGFP.…”
Section: Resultsmentioning
confidence: 99%
“…The recombinant Th2P-4M virus harbours the same genetic background as Tha apart from bearing two mutations in the viral P-protein (W265G, M287V) and four mutations in the viral M-protein (R77K, D100A, A104S, M110L) which were previously described (10,31,32). To monitor viral infection, recombinant viral Tha-eGFP and Th2P-4M-eGFP constructs were used which were generated by cloning sequences of eGFP (recovered from pEGFP-C1 plasmid, Promega) into the genetic sequence of Tha (35) and Th2P-4M, respectively. Viral strains were sequenced before used for infection experiments.…”
Section: Virusesmentioning
confidence: 99%
“…To sum up this section, proteins that interacts with this hot disordered loop are connected to lipids (membrane), particularly with phosphatidylinositol, and the regulation of bindings is made by phosphorylation. Recently, Besson et al (2019) identified that mitogen-activated protein kinase pathway and phosphatidylinositol metabolism are involved in the later stage of RABV infection.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, mutant proteins linked to familial forms of neurodegenerative diseases including huntingtin, superoxide dismutase 1, tau, and spastin were all found to cause FAT deficits through a mechanism involving deregulation of selected kinase pathways (reviewed in Morfini et al, 2009a ; Brady and Morfini, 2010 ). Relevant to the topics discussed in this review, neurotropic viruses have been widely shown to modulate the activity of host kinases (Zachos et al, 1999 ; Piacentini et al, 2015 ; Bonjardim, 2017 ; Besson et al, 2019 ), including some involved in the regulation of FAT. A thorough description of these findings is beyond the scope of this review, but some relevant examples are provided below.…”
Section: Neuronal Kinases: Potential Role On Axonal Transport Of Neurotropic Viruses and Pathological Implicationsmentioning
confidence: 99%
“…Given the number of kinases activated at different stages of the viral cycle and the complexity and crosstalk among kinase pathways, the identification of pathologically relevant ones may represent a major challenge for investigators (Besson et al, 2019 ). Nevertheless, a message of hope is provided by the successful development of highly specific, brain-permeable kinase inhibitors (Maphis et al, 2016 ), and increasing experimental evidence confirming a role of host kinases on the neuronal pathology triggered by some viruses (Beckham et al, 2007 ).…”
Section: Neuronal Kinases: Potential Role On Axonal Transport Of Neurotropic Viruses and Pathological Implicationsmentioning
confidence: 99%